OBJECTIVES OF ECONOMIC DEVELOPMENT IN THE CONDITIONS OF GLOBALIZATION (American Journal of Business Management, Economics and Banking, 2022)
The rise in the economy of many countries indicates that countries are developing development programs consisting of many components ¬, in which at first glance everything is justified, but the desired goal is not always achieved during their implementation. In this regard, there is a need to develop the foundations of a development strategy. A strategy is a plan of action to achieve a desired goal. A strategy becomes necessary when there are not enough available resources to achieve the goal. In the conditions of their limitation, its main task is the efficient use of resources to achieve the main goal.